1970
DOI: 10.1085/jgp.55.6.703
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sodium Current in the Radial Spread of Contraction in Frog Muscle Fibers

Abstract: The membrane potential of isolated muscle fibers was controlled with a two-electrode voltage clamp, and the radial extent of contraction elicited by depolarizing pulses of increasing magnitude was observed microscopically. Depolarizations of the fiber surface only 1-2 mv greater than the contraction threshold produced shortening throughout the entire crosssection of the muscle fiber. The radial spread of contraction was less effective in fibers exposed to tetrodotoxin or to a bathing medium with a greatly redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(67 citation statements)
references
References 10 publications
4
63
0
Order By: Relevance
“…1 will show that this model is distinguished by the absence of a circuit element to represent the resistance of the solution in the lumen of the tubules. The lumped model then predicts that there should be no radial gradients of potential within the tubular system in disagreement with the straightforward interpretation of the experimental results of GonzAlezSerratos, 1971;Adrian, Costantin, and Peachey, 1969;Costantin, 1970;and b.…”
Section: Lumped Model Of the Tubular Systemmentioning
confidence: 83%
See 1 more Smart Citation
“…1 will show that this model is distinguished by the absence of a circuit element to represent the resistance of the solution in the lumen of the tubules. The lumped model then predicts that there should be no radial gradients of potential within the tubular system in disagreement with the straightforward interpretation of the experimental results of GonzAlezSerratos, 1971;Adrian, Costantin, and Peachey, 1969;Costantin, 1970;and b.…”
Section: Lumped Model Of the Tubular Systemmentioning
confidence: 83%
“…There are a number of theoretical papers which claim, however, that circumferential and radial potential gradients should exist and be significant in cylindrical muscle fibers (Eisenberg and Johnson, 1970;Barcilon et al, 1971;Peskoff et al, 1972; a review of the literature can be found in Peskoff and Eisenberg, 1973). There are some indirect indications of circumferential and radial potential gradients in the experiments of Adrian, Costantin, and Peachey (1969) and Costantin (1970) but there has been no direct experimental evidence concerning the existence of these effects, let alone their quantitative significance, and so we thought it worthwhile to seek such evidence. Impedance measurements were made by the techniques described by Valdiosera et al, 1974 a. Measurements were made at two different circumferential positions of the voltage microelectrode, the longitudinal position being constant, and the radial position being unknown.…”
Section: Circumferential Variation Of Potential Experimental Evidencementioning
confidence: 99%
“…Besides, the delayed current in the skeletal muscle fibre is apparently also decreased in presence of tetrodotoxin. Such an effect is rather surprising; it might perhaps result from some regenerative activity in the tubule membrane as suggested by Costantin (1970) …”
Section: Discussionmentioning
confidence: 98%
“…The electrical conduction in the transverse tubules has recently been shown to be a regenerative process (Costantin, 1970;Costantin & S. R. , similar to the longitudinal propagation along the surface membrane but with much lower safety factor (R. H. Adrian & Peachey, 1973), and this accounts for the remarkable speed with which the onset of shortening spreads inwards within each fibre (GonzalezSerratos, 1971). …”
Section: Activation Of the Contractile Materialsmentioning
confidence: 99%